2018
DOI: 10.1177/1055665617744062
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nasoalveolar Molding on Nasal Airway Anatomy

Abstract: NAM effectively molds the external nasal cartilage and structures but may have limited effects on internal nasal structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Tomohisa et al 20 classified the positions of nasal septal deviations into 3 categories: anterior, middle, and posterior, he pointed out that classified the positions of nasal septal deviations into 3 categories: anterior, middle, and posterior. Massie et al 18 used a similar method to divide the position of the nasal septal deviation into 2 types anterior and posterior, and got similar results. In our study most sever deviations were discovered in middle part of nasal septum in both coronal and transverse level.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Tomohisa et al 20 classified the positions of nasal septal deviations into 3 categories: anterior, middle, and posterior, he pointed out that classified the positions of nasal septal deviations into 3 categories: anterior, middle, and posterior. Massie et al 18 used a similar method to divide the position of the nasal septal deviation into 2 types anterior and posterior, and got similar results. In our study most sever deviations were discovered in middle part of nasal septum in both coronal and transverse level.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, CBCT shows plenty of advantages, such as low radiation dose, isotropic voxel size, and easy accessibility. 18 The maxillary sinus varies with the age of the patients, which leads to a bias when we talk about the asymmetry. Angle of septal deviation and RSA were commonly used parameters in previous studies to evaluate the degree of the nasal septal deviation 6,17,19 These kinds of parameters using angle or ratio to manifest degree of asymmetry avoid the bias caused by individual difference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CBCT was also used to evaluate maxillary expansion in CLP patients [6,[30][31][32][33][34][35][36]. Moreover, CBCT was also used in various anatomical studies related with CLP patients: 1) Three-dimensional (3D) analysis of craniofacial structures [3,29,37], and of facial asymmetry [29,38,39]; 2) mandible [3,29,40,41]; 3) sella turcica [42]; 4) pharyngeal airway volume [3,[43][44][45][46][47][48]; 5) cortical bone thickness around the cleft area [26,27,29,49]; 6) palatal morphology and soft tissue depth [6,28,29,50,51]; 7) maxillary sinus volume [29,52,53]; 8) nasal morphology [3,29,54], and nasal airway [55]; 9) canine eruption through the alveolar graft bone [3,4,6,7,27,…”
Section: Introductionmentioning
confidence: 99%
“…The diversity of study models, evaluation times, size and heterogeneity of the samples, different protocols performed, and poorly detailed descriptions of the methods make it difficult to safely evaluate studies that use the NAM protocol 13 . Among the methods used by studies to assess the effects of NAM therapy are the use of 2-dimensional images, 7,10,14,16,17 and even 3-dimensional records 18–24 . Results of the studies have shown improvement in the aesthetics of the nose, lip, alveolar bone, palate, and nasal wings 14 .…”
mentioning
confidence: 99%